Analysis of spontaneous reports of adverse reactions, developed in the use of drugs during pregnancy - E. O. Zhuravleva; N. Yu. Velts; K. E. Zatolochina; S. V. Glagolev; V. A. Polivanov; M. A. Darmostukova; V. K. Lepakhin; B. K. Romanov; R. N. Alyautdin (Безопасность и риск фармакотерапии, 2018)
The article presents data obtained in a retrospective analysis of spontaneous messages (SM) on drug adverse reactions during pregnancy, recieved in the Russian base «Pharmacovigilance» AIS Roszdravnadzor, for the period 1 January 2015 to 31 December 2015 included.